Remote monitoring improves outcome after ICD implantation: the clinical efficacy in the management of heart failure (EFFECT) study. Issue 8 (4th April 2015) - De Simone, Antonio; Leoni, Loira; Luzi, Mario; Amellone, Claudia; Stabile, Giuseppe; La Rocca, Vincenzo; Capucci, Alessandro; D'onofrio, Antonio; Ammendola, Ernesto; Accardi, Francesco; Valsecchi, Sergio; Buja, Gianfranco
Abstract : Aims: Internet-based remote interrogation systems have been shown to reduce emergency department and in-office visits in patients with implantable cardioverter defibrillators (ICDs), resulting in increased efficiency for healthcare providers. Nonetheless, studies sized to demonstrate the impact of remote monitoring on patients' outcome have been lacking. Methods and results: The EFFECT study was a multicentre clinical trial aimed at measuring and comparing the outcome of ICD patients conventionally followed-up by means of in-clinic visits (Standard arm) or by remote monitoring (Remote arm) in the clinical practice of 25 Italian centres. From 2011 to 2013, 987 consecutive patients were enrolled and followed up for at least 12 months. The primary endpoint was the rate of death and cardiovascular hospitalizations. Remote monitoring was adopted by 499 patients. Patients in the Standard and Remote arms did not differ significantly in terms of baseline clinical characteristics, except for a more frequent use of ICD with cardiac resynchronization therapy (CRT-D) in the Remote arm (48 vs. 36%, P < 0.001). One-year rates of the primary combined endpoint were 0.27 events/year for patients in the Standard arm and were 0.15 events/year for those in the Remote arm (incident rate ratio, 0.55; 95% CI, 0.41–0.73; P < 0.001). The endpoint rates in the Standard and Remote arms were 0.27 and 0.08 events/year, respectively, among CRT-D recipients ( P < 0.001), and 0.28 vs. 0.21 among ICD patients ( P = 0.094). The rates of in-office visits were 1.9 per year in the Standard arm and 1.7 per year in the Remote arm. Conclusion: Compared with the standard follow-up through in-office visits, remote monitoring is associated with reduced death and cardiovascular hospitalizations in patients with ICD in clinical practice. Clinical Trial Registration: URL: http://clinicaltrials.gov/ Identifier: NCT01723865.